Les natures du jardin d’installation - Nicole Valois (Projets de Paysage)
Through garden festivals such as the International Garden Festival (Reford Gardens), in Grand-Métis, Québec, professional landscapers and landscape architects have founded a new form of expression. As to knowing whether we are in the presence of a garden or a work of art, considering that, theoretically, each is examined differently, there is much to cover on the subject. This article addresses the meaning of installation gardens by using a model which opens on a multidimensional reading cross-referencing the disciplines of art, garden art, and landscape architecture. This is John Dixon Hunt’s theory of the gradation of three natures, specific to the study of Renaissance and Baroque gardens. The article examines two cases and shows how their creators use traditional garden or art processes to express a contemporary vision of nature and the environment, at the first and second degrees.